Evaluasi Pembelajaran dari Perspektif Pedagogi - Adam, Mohammad Fani; Purwohadi, Purwohadi; Widyaningsih, Eka; Carsiwan, Carsiwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to evaluate learning from a pedagogical perspective. The method used in this research is a Systematic Literature review (SLR) using PRISMA 2020 guidelines, electronic databases used for searching, ERIC, Taylor and Francis Online, SCOPUS, PUBMED, Google Scholar, and SCIENCE Direct. The number of articles reviewed was four in the form of articles and theses. The results of this research found that the evaluation method in the pedagogical approach plays an important role in measuring student learning achievement as a whole. The pedagogical approach emphasizes student-centered learning, where the teacher is a facilitator and guide. In this context, several evaluation methods have been developed to suit this pedagogical approach. In conclusion, based on the principles of the pedagogical approach in learning evaluation, educators can create a learning environment that supports and encourages academic progress and holistic development of students. Keywords: learning evaluation, pedagogy, Systematic Literature review (SLR),